Phylogeny and expression modulation of interleukin 1 receptors in grass carp (Ctenopharyngodon idella). (October 2019) - Gao, Jingduo; Jiang, Xinyu; Wang, Junya; Xue, Yujie; Li, Xia; Sun, Zhaosheng; Xie, Haixia; Nie, Pin; Zou, Jun; Gao, Qian
Abstract: The interleukin (IL) −1 family members play an important role in regulating inflammatory responses and their functions are mediated by a group of receptors consisting of immunoglobulin and Toll/IL-1 receptor (TIR) domains. In humans, 10 IL-1Rs are found. In this study, 5 IL-1 receptors including IL-1R3/IL-1RAcP, IL-1R8/SIGIRR, IL-1R9a/IL-1RAcPL1a, IL-1R9b/IL-1RAcPL1b and IL-1R10/IL-1RAcPL2 were identified in grass carp ( Ctenopharyngodon idella ). Phylogenetic analysis reveals that the IL-1R9a/IL-1RAcPL1a and IL-1R9b/IL-1RAcPL1b share significantly high sequence similarity and are believed to have been duplicated from the same gene prior to the radiation of teleosts. Further, these two receptors closely relate to the IL-1R10/IL-1RAcPL2, suggesting that they may have evolved from a common ancestor. The IL-1R3/IL-1RAcP, IL-1R9a/IL-1RAcPL1a, IL-1R9b/IL-1RAcPL1b and IL-1R10/IL-1RAcPL2 are highly expressed in the brain. Stimulation of primary spleen leucocytes by LPS and intraperitoneal injection of fish with poly (I:C) or bacterial infection results in significant increases of IL-1R3/IL-1RAcP expression. Interestingly, the IL-1R8/SIGIRR and IL-1R10/IL-1RAcPL2 showed similar expression patterns. Highlights: Five IL-1 receptor family members were identified in grass carp. Two duplicated IL-1R9/IL-1RAcPL1 genes exist in grass carp and are highly expressed in the brain. IL-1R9/IL-1RAcPL1 and IL-1R10/IL-1RAcPL2 evolved from a common ancestor before jawed vertebrates. Grass carp IL-1R10/IL-1RAcPL2 and IL-1R8/SIGIRR exhibit similar expression patterns.